Lithium-free battery and preparation method thereof
By forming a lithium-metal alloy layer and a lithium plating layer on a metal substrate without lithium batteries, the problem of low electrodeposition density of the lithium plating layer is solved, significantly improving the battery life and side reactions, and achieving more efficient battery performance.
Patent Information
- Application Number
- CN202180005836.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-21
- Filing Date
- 2021-05-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-05-07
AI Technical Summary
The lithium plating layer formed on the negative electrode of the existing lithium-free batteries has a low electrode density, resulting in rapid deterioration of life characteristics and side reaction problems of electrolyte.
Using a lithium-free battery design containing a specific metal substrate, the lithium-metal alloy layer and lithium plating layer are formed on the metal substrate to ensure the electrodeposition density of the lithium plating layer is improved, and the lithium-metal alloy layer is formed by charging to improve the negative electrode activity. The capacity of the material.
The electrodeposition density of lithium plating is improved, the side reactions of electrolyte are reduced, and the life characteristics of lithium-free batteries are significantly improved.
Smart Images

Figure GDA0005127724820000141 
Figure GDA0005127724820000151
Abstract
Description
Technical Field
[0001] CROSS REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0055157 filed on May 8, 2020, and Korean Patent Application No. 10-2021-0008511 filed on January 21, 2021, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present disclosure relates to a lithium-free battery and a method for preparing the same. Background Art
[0004] Due to the rapid increase in the use of fossil fuels, there is a growing demand for the use of alternative or clean energy, among which the most active research areas are the power generation and storage of electricity using electrochemistry.
[0005] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of their use tends to be gradually expanded.
[0006] Recently, with the increase in technology development and demand for mobile devices such as portable computers, mobile phones and cameras, the demand for secondary batteries as energy sources has grown rapidly. Among such secondary batteries, many studies have been conducted on lithium secondary batteries, which exhibit high energy density and working potential, long cycle life and low self-discharge rate, and have been commercialized and widely used.
[0007] Generally speaking, a lithium secondary battery has a structure in which a non-aqueous electrolyte is impregnated into an electrode assembly comprising a positive electrode, a negative electrode and a porous separator. In addition, the positive electrode is usually made by coating a positive electrode mixture containing a positive electrode active material on an aluminum foil, and the negative electrode is made by coating a negative electrode mixture containing a negative electrode active material on a copper foil.
[0008] Generally, lithium transition metal oxides are used as positive electrode active materials, and carbon-based materials are used as negative electrode active materials.
[0009] Recently, however, lithium metal batteries that use lithium metal itself as the negative electrode active material have been commercialized. In addition, lithium-free batteries that use only a current collector as the negative electrode when preparing the electrode, supply lithium from the positive electrode by charging, and use lithium metal as the negative electrode active material are being actively studied. From the perspective of high energy density, lithium-free batteries are considered to be a battery concept that can achieve the highest energy density.
[0010] However, in the above negative electrode, a lithium plating layer is formed on the current collector by electrodeposition caused by charging. At this time, a lithium plating layer with a low electrodeposition density is formed on the current collector, and the side reaction of the electrolyte is serious, resulting in rapid deterioration of life characteristics.
[0011] Therefore, it is necessary to develop a lithium-free battery that can solve the above problems and increase the electrodeposition density of the lithium plating layer. Summary of the invention
[0012]
Technical issues
[0013] Therefore, the present disclosure is intended to solve the above-mentioned problems and other technical problems that have not yet been resolved.
[0014] Specifically, an object of the present disclosure is to provide a lithium-free battery in which a lithium plating layer having a high electrodeposition density can be formed on a negative electrode by a simpler method.
[0015] Another object of the present disclosure is to prevent side reactions of lithium-free batteries, thereby improving lifespan characteristics.
[0016]
Technical solution
[0017] To achieve the above-mentioned object, according to one embodiment of the present disclosure, there is provided a lithium-free battery comprising a positive electrode, a negative electrode, a separator and a lithium non-aqueous electrolyte, wherein the negative electrode comprises a metal substrate, the metal substrate comprises at least one metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd, P and Hg; a lithium-metal alloy layer formed on the metal substrate; and a lithium plating layer formed on the lithium-metal alloy layer, wherein the metal contained in the lithium-metal alloy layer is the metal contained in the metal substrate.
[0018] The lithium-metal alloy layer and the lithium plating layer may be formed by charging the lithium-free battery.
[0019] At this time, the unit area capacity (mAh / cm 2 ) may be greater than the capacity per unit area of the negative electrode.
[0020] The metal substrate may include at least one metal selected from the group consisting of Si, Ge, Sn, Sb, Mg, Bi, As, Pb, P, and Zn.
[0021] The metal substrate may have a thickness of 3 μm to 100 μm.
[0022] The metal substrate may have a thickness of 10 μm to 80 μm.
[0023] The lithium-metal alloy layer and the lithium plating layer may each have a thickness of 0.1 μm or more.
[0024] According to one embodiment of the present disclosure, there is provided a method for preparing the lithium-free battery, the method comprising the following steps: (a) forming a positive electrode mixture layer on at least one surface of a positive electrode current collector to prepare a positive electrode; (b) preparing a preliminary negative electrode composed of a metal substrate, the metal substrate comprising at least one metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd, P and Hg; (c) arranging a separator between the positive electrode and the preliminary negative electrode to prepare an electrode assembly; and (d) loading the electrode assembly and the lithium non-aqueous electrolyte into a battery case, sealing the battery case, and then charging the battery, wherein the capacity per unit area (mAh / cm 2 ) is greater than the capacity per unit area of the negative electrode.
[0025] The metal substrate may include at least one metal selected from the group consisting of Si, Ge, Sn, Sb, Mg, Bi, As, Pb, P, and Zn.
[0026] The metal substrate may have a thickness of 3 μm to 100 μm. DETAILED DESCRIPTION
[0027] Hereinafter, the present disclosure will be described in more detail to facilitate understanding of the present invention.
[0028] The terms and words used in this specification and claims should not be interpreted as limited to the commonly used meanings or meanings in dictionaries, but should be interpreted in the meaning and concept consistent with the technical scope of the present invention based on the principle that the inventor has appropriately defined the concepts of the terms in order to describe the present invention in the best manner.
[0029] The terminology provided herein is for the purpose of describing particular embodiments only and is not intended to limit the present disclosure.The singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0030] Furthermore, throughout the specification, when a certain part is referred to as “comprising” certain components, unless otherwise specified, it means that the part may further include other components, and does not exclude other components.
[0031] According to one embodiment of the present disclosure, there is provided a lithium-free battery comprising a positive electrode, a negative electrode, a separator and a lithium non-aqueous electrolyte, wherein the negative electrode comprises a metal substrate, the metal substrate comprises at least one metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd, P and Hg; a lithium-metal alloy layer formed on the metal substrate; and a lithium plating layer formed on the lithium-metal alloy layer, wherein the metal contained in the lithium-metal alloy layer is the metal contained in the metal substrate. At this time, the metal substrate may comprise at least one metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd, P and Hg.
[0032] For such a lithium-free battery, it is important to eventually increase the electrodeposition density of the lithium plating layer. The increase in electrodeposition density reduces the specific surface area, thereby minimizing the side reactions of the electrolyte, which can improve the life characteristics of the lithium-free battery.
[0033] Specifically, the negative electrode of the present disclosure is in the form of a preliminary negative electrode prepared using a metal substrate, which is used to prepare a lithium-free battery, and then charged to form a lithium-metal alloy layer and a lithium plating layer, which is used as a negative electrode. Therefore, the lithium-metal alloy layer and the lithium plating layer can be formed by charging the lithium-free battery.
[0034] When a battery is prepared using the preliminary negative electrode made of a metal substrate and charged, Li ions transferred from the positive electrode through the lithium nonaqueous electrolyte chemically react with the metal substrate to form a lithium-metal alloy layer on the metal substrate.
[0035] Therefore, the metal substrate should be a metal substrate capable of forming an alloy with lithium, and the materials described above can be used.
[0036] On the other hand, the higher the degree of alloying with lithium, more specifically the higher the volume energy density of the metal, the more the metal reacts with lithium relative to the same volume, thereby forming more alloy layers. In such a case, the electrodeposition density of the lithium plating layer formed later can be further increased.
[0037] Therefore, among the metal substrates, it is more preferable to be formed of a material having a higher volume energy density and forming more lithium alloy layers. In detail, the metal substrate may include at least one metal selected from the group consisting of Si, Ge, Sn, Sb, Mg, Bi, As, Pb, P and Zn. In this case, the metal substrate may be formed of at least one metal selected from the group consisting of Si, Ge, Sn, Sb, Mg, Bi, As, Pb, P and Zn. Such a metal may correspond to a material having a higher degree of lithium alloy than Al, that is, a material with a high volume energy density.
[0038] On the other hand, since the reaction area of the metal substrate is fixed, the lithium-metal alloy layer is formed up to a predetermined portion during charging, and the capacity per unit area (mAh / cm 2 ) is greater than the capacity per unit area of the negative electrode. Therefore, during subsequent charging, the alloying reaction between lithium and metal does not proceed further, and a lithium plating layer is formed on the lithium-metal alloy layer, and the lithium on the lithium-metal alloy layer and the lithium in the lithium plating layer serve as negative electrode active materials.
[0039] That is, for the negative electrode, a metal substrate is used to prepare the battery, and then the lithium accepted by charging is used as an active material. Therefore, in order to increase the capacity of the lithium-free battery, it is necessary to increase the capacity of the positive electrode so that not only a lithium-metal alloy layer but also a lithium plating layer is formed, which can be achieved by increasing the amount of lithium used as the negative electrode active material.
[0040] On the other hand, conventionally, the electrodeposition density of the lithium plating layer is low, and therefore there are problems such as side reactions of the electrolyte, which greatly limits its use. However, according to the present disclosure, the lithium-metal alloy layer can be formed between the lithium plating layer and the metal substrate, thereby increasing the electrodeposition density of the lithium plating layer. Therefore, the present disclosure can be configured to increase the capacity per unit area (mAh / cm 2 ) is greater than the capacity per unit area of the negative electrode, thereby being able to increase the electrodeposition density of the lithium plating layer while improving the total capacity of the lithium-free battery, thereby improving the life characteristics.
[0041] Here, the capacity per unit area of the positive electrode can be calculated by multiplying the actual apparent capacity (mAh / g) of the positive electrode active material by the amount of the active material (g) and dividing it by the area of the current collector (cm 2 ) to calculate.
[0042] In addition, the capacity per unit area of the negative electrode refers to the capacity that is developed when lithium and metal are alloyed. The capacity per unit area of the negative electrode can be calculated based on the amount of the lithium-metal alloy layer that can be formed on the metal substrate.
[0043] The metal substrate may comprise the metal as described above, wherein the term 'comprising' means containing the metal at a level of 100%, or containing other metals and oxides as inevitable impurities at a level of 5 wt %, 3 wt %, or further at a level of 1 wt % or less.
[0044] The metal substrate may have a thickness of 3 μm to 100 μm, particularly 10 μm to 80 μm, 10 μm to 60 μm, and more particularly 30 μm to 60 μm.
[0045] When the metal substrate has an excessively thin thickness outside the above range, the thickness becomes too thin due to the alloying reaction with lithium, resulting in a problem of reduced strength, forming a very thin lithium-metal alloy layer, forming many lithium plating layers, and the specific surface area of the lithium plating layers increases, so that many electrolyte side reactions also occur, thereby failing to achieve the effect of the present disclosure. On the contrary, when the metal substrate is too thick, the overall volume increases, so that the volume energy density decreases, which is undesirable from a volume perspective.
[0046] On the other hand, the negative electrode in the lithium-free battery according to the present disclosure mainly comprises a lithium-metal alloy layer and a lithium plating layer, and the thickness thereof is not particularly limited, but the thickness of each layer can be at least 0.1 μm or more, particularly 1 μm or more, and more particularly 3 μm or more.
[0047] This is also related to the thickness of the metal substrate and is also due to the different unit area capacity between the positive electrode and the negative electrode. Therefore, the thickness of each of the lithium-metal alloy layer and the lithium plating layer can vary depending on the construction method of the battery. In addition, the thickness is also affected by the thickness of the metal substrate. When the thickness of the lithium-metal alloy layer is outside the above range and is too thin, the lithium plating layer, which is fragile to the reaction with the electrolyte, becomes too thick, thereby forming many by-products, and the internal resistance of the battery increases rapidly, which is not preferred.
[0048] In addition, when the lithium plating layer is too thin, the lithium-metal alloy layer becomes too thick, and the alloy disappears during discharge, causing the lithium-metal alloy layer and the metal substrate to disintegrate. When recharging, the lithium-metal alloy is not fully generated on the metal substrate, making the lithium plating layer irregular, and it is also difficult to increase the electrodeposition density, so that the life deterioration can be accelerated, which is not preferred. Of course, in such a case, the battery capacity will also decrease, and although the advantage of the lithium-free battery is that the energy density is high, it becomes difficult to maximize it.
[0049] On the other hand, according to another embodiment of the present disclosure, there is provided a method for preparing the lithium-free battery, the method comprising the following steps: (a) forming a positive electrode mixture layer on at least one surface of a positive electrode current collector to prepare a positive electrode; (b) preparing a preliminary negative electrode composed of a metal substrate, the metal substrate comprising at least one metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd, P and Hg; (c) arranging a separator between the positive electrode and the preliminary negative electrode to prepare an electrode assembly; and (d) loading the electrode assembly and the lithium non-aqueous electrolyte into a battery case, sealing the battery case, and then charging the battery, wherein the capacity per unit area (mAh / cm 2 ) is greater than the capacity per unit area of the negative electrode. In this case, the metal substrate may include at least one metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd, P and Hg.
[0050] Here, as described above, the metal substrate may specifically include at least one metal selected from the group consisting of Si, Ge, Sn, Sb, Mg, Bi, As, Pb, P, and Zn, and may have a thickness of 3 μm to 100 μm. Here, the metal substrate may be made of at least one metal selected from the group consisting of Si, Ge, Sn, Sb, Mg, Bi, As, Pb, P, and Zn.
[0051] Other specific details are the same as above.
[0052] That is, the lithium-free battery according to the present disclosure is prepared by using a metal substrate as a preliminary negative electrode, using it to prepare an electrode assembly, and then loading the electrode assembly into a battery case together with a lithium non-aqueous electrolyte, and sealing the battery case, and then charging, thereby forming a lithium-metal alloy layer and a lithium plating layer on the metal substrate. In addition, as described above, in order to have such a structure, the unit area capacity of the positive electrode can be set to be greater than the unit area capacity of the negative electrode.
[0053] On the other hand, other components of the lithium-free battery will be described.
[0054] As described above, the positive electrode is prepared by forming a positive electrode mixture layer on at least one surface of the positive electrode current collector. Here, the positive electrode mixture layer includes a positive electrode active material, a binder and a conductive material, and may optionally further include a filler.
[0055] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector may have a thickness of 3 μm to 500 μm, and may have fine concavoconvexities formed on the surface of the current collector to increase the adhesion of the positive electrode active material. For example, it can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0056] The positive electrode active material as the active material may be, for example, a layered compound such as lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; lithium manganese oxide, for example, a chemical formula Li 1+x Mn 2-x O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5 and Cu2V2O7; 1-x M x Nickel-site lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); represented by the chemical formula LiMn 2-x M x Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (wherein M = Fe, Co, Ni, Cu or Zn); LiMn2O4, a part of Li in the chemical formula is replaced by alkaline earth metal ions; disulfide; Fe2(MoO4)3, etc., are not limited thereto, and materials known in the art can be used.
[0057] The binder is a component that helps to bind the active material, the conductive material, etc. and to the current collector. Generally, the added amount can be 0.1 to 30% by weight, particularly 1 to 10% by weight, and more particularly 1 to 5% by weight based on the total weight of the positive electrode mixture layer. Examples of the binder may include polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, various copolymers, etc.
[0058] The amount of the conductive material added is generally 0.1 to 30% by weight, particularly 1 to 10% by weight, and more particularly 1 to 5% by weight, based on the total weight of the positive electrode mixture layer. The conductive material is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery, for example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as fluorocarbon powders, aluminum powders or nickel powders; conductive whiskers of zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives.
[0059] The filler is not particularly limited as long as it is a fibrous material that does not cause chemical changes in a corresponding battery, for example, an olefin-based polymer such as polyethylene or polypropylene; and a fibrous material such as glass fiber or carbon fiber are used.
[0060] The separator is an insulating film with high ion permeability and mechanical strength. The pore size of the separator is generally 0.01 μm to 10 μm, and the thickness is generally 5 μm to 300 μm. As such a separator, for example, a chemically resistant and hydrophobic olefin polymer such as polypropylene; a sheet or non-woven fabric made of glass fiber or polyethylene, etc. are used. When a solid electrolyte such as a polymer is used as an electrolyte, the solid electrolyte can also serve as a separator.
[0061] The lithium non-aqueous electrolyte generally includes a lithium salt and a non-aqueous solvent. As the non-aqueous solvent, a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, etc. are used, but it is not limited thereto.
[0062] As examples of nonaqueous electrolytes, there can be mentioned aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate.
[0063] Examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ion dissociative groups, and the like.
[0064] Examples of the inorganic solid electrolyte include nitrides, halides and sulfates of lithium (Li), such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2.
[0065] The lithium salt is a material that is easily soluble in the non-aqueous electrolyte. The lithium salt may include, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate and lithium imide.
[0066] In addition, in order to improve the charge / discharge characteristics, flame retardancy, etc., the nonaqueous electrolyte may further contain, for example, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N, N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum chloride, etc. In some cases, in order to impart non-flammability, the electrolyte may also include a halogen-containing solvent such as carbon tetrachloride and trifluoroethylene. In addition, in order to improve high temperature retention characteristics, the electrolyte may also include carbon dioxide gas. In addition, it may also include fluoroethylene carbonate (FEC), propylene sultone (PRS), etc.
[0067] The battery case is not limited as long as it has a structure capable of accommodating the electrode assembly, and may be a pouch-type battery case known in the art, or a prismatic or cylindrical battery case made of a metal can.
[0068] The charging may be full charging, and then aging treatment is performed at high temperature and / or room temperature. Thus, a lithium-metal alloy layer and a lithium plating layer are formed on the metal substrate of the prepared negative electrode.
[0069] The preferred embodiments of the present disclosure, the comparative examples for comparison therewith, and the test examples for evaluating them are described below. However, it is obvious to those skilled in the art that these embodiments are only examples of the present disclosure, and various changes and modifications can be made within the scope and technical spirit of the present disclosure, and it goes without saying that such changes and modifications fall within the scope of the appended claims.
[0070] <Example 1>
[0071] Using lithium transition metal oxides (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) as the positive electrode active material, PVdF as the binder, and Super-P as the conductive material. The positive electrode active material: binder: conductive material were added to NMP at a weight ratio of 96:2:2 to produce an active material slurry, which was then heated to 4 mAh / cm per side. 2 The resulting film was coated on an Al foil, dried in a dryer at 130° C. under an air atmosphere, and then rolled to prepare a positive electrode.
[0072] As the preliminary negative electrode, a Si foil having a thickness of 30 μm, a length of 40 mm, and a width of 60 mm was used.
[0073] An SRS separator with a thickness of 20 μm was assembled on the positive electrode and the prepared negative electrode using a stacking method, the assembled electrodes were loaded into an aluminum bag-type battery case, and a solution of fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) with a volume ratio of 3:7 in which 1 M LiFSI was dissolved was injected, and then the battery case was sealed to prepare a single cell.
[0074] <Example 2>
[0075] A lithium-free battery was prepared in the same manner as in Example 1, except that a Si foil having a thickness of 60 μm was used as the preliminary negative electrode in Example 1.
[0076] <Example 3>
[0077] A lithium-free battery was prepared in the same manner as in Example 1, except that a Sn foil having a thickness of 30 μm was used as the preliminary negative electrode in Example 1.
[0078] <Example 4>
[0079] A lithium-free battery was prepared in the same manner as in Example 1, except that an Al foil having a thickness of 30 μm was used as the preliminary negative electrode in Example 1.
[0080] <Comparative Example 1>
[0081] A lithium-free battery was prepared in the same manner as in Example 1, except that a Cu foil having a thickness of 30 μm was used as the preliminary negative electrode in Example 1.
[0082] <Comparative Example 2>
[0083] A lithium-free battery was prepared in the same manner as in Example 1, except that a foil containing 10 wt % of Si as a dopant in a Cu matrix having a thickness of 30 μm was used as the preliminary negative electrode in Example 1.
[0084] <Comparative Example 3>
[0085] A lithium-free battery was prepared in the same manner as in Example 1, except that a foil obtained by plating a 1 μm-thick Sn foil on a 30 μm-thick Ni foil by electroless plating was used as the preliminary negative electrode in Example 1.
[0086] <Experimental Example 1>
[0087] The load amounts of the positive electrodes and negative electrodes used in Examples 1 to 4 and Comparative Examples 1 to 3 were measured as described below.
[0088] In order to measure the positive electrode load, the positive electrode prepared in Example was punched into 1.6 cm 2 The discharge capacity is measured by charging and discharging a Li metal electrode at a rate of 0.1 C using a coin-shaped battery as the counter electrode. The positive electrode load can be calculated by dividing the measured discharge capacity by the area of the positive electrode.
[0089] In order to measure the load of the negative electrode, the negative electrode prepared in Example was punched into 1.6 cm 2 The coin shape of the negative electrode was used, and the Li metal electrode was used as the counter electrode to charge and discharge at a rate of 0.1C, and the discharge capacity was measured based on the time until the lithium-metal was alloyed. The load of the negative electrode can be calculated by dividing the measured discharge capacity by the area of the negative electrode.
[0090] The positive electrode loading amount and the negative electrode loading amount calculated in this way are shown in Table 1 below.
[0091]
Table 1
[0092]
[0093] Referring to Table 1, it can be confirmed that the capacity per unit area of the positive electrode is greater than the capacity per unit area of the negative electrode. It can be seen that the lithium-free battery prepared using such a positive electrode and a negative electrode is charged by the capacity per unit area of the positive electrode, a lithium-metal alloy layer is formed on the metal substrate by the capacity per unit area of the negative electrode, and a lithium plating layer is formed by the remaining capacity. In addition, in the case of copper, it can be seen that alloying with lithium is not performed.
[0094] <Experimental Example 2>
[0095] The lithium-free batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were charged under the following conditions and then disassembled to calculate the thickness and electrodeposition density of the lithium plating layer formed on the negative electrode. The results are shown in Table 2 below.
[0096] Charging: 0.2C, CC / CV, 4.25V, 1 / 20C cutoff
[0097] For the thickness of the lithium plating layer, the average value of the thickness is obtained by selecting two arbitrary points, and the electrodeposition density of the lithium plating layer is digitized by calculating the deposition mass and deposition volume.
[0098]
Table 2
[0099]
[0100] (Theoretical density of lithium metal: 0.54g / cm 3 )
[0101] Referring to Table 2, when the metals of Examples 1 to 4 according to the present disclosure are used, the thickness of the lithium plating layer is thin and the density is improved, confirming that the lithium plating layer is formed more densely. On the other hand, it is confirmed that Comparative Example 1 using Cu has almost no improvement in the electrodeposition density, and even when a metal as defined herein is included as a dopant (Comparative Example 2), or even when it is formed in a very thin range (Comparative Example 3), the result of fully improving the electrodeposition density cannot be obtained. It can be seen that in order to fully increase the electrodeposition density of the lithium plating layer and thus improve the battery performance, the amount of metal required is capable of alloying a sufficient amount of lithium, and the metal should be formed as a whole to improve the electrodeposition density of the lithium plating layer over the entire area.
[0102] On the other hand, Example 4 using Al has a predetermined effect of improving the electrodeposition density, but the improvement effect is smaller than that of Si, Sn, etc. in Examples 1 to 3.
[0103] <Experimental Example 3>
[0104] The lithium-free batteries of Examples 1 to 4 and Comparative Examples 1 to 3 were charged and discharged at 0.2 C, and the 1-time discharge capacity was measured. Charging and discharging were additionally performed under the following conditions, and then the 100-time discharge capacity retention rate relative to the 1-time discharge capacity was calculated, and the results are shown in Table 3 below.
[0105] Charging: 0.2C, CC / CV, 4.25V, 1 / 20C cutoff
[0106] Discharge 0.5C, CC, 3.0V, cut-off
[0107]
Table 3
[0108] 1 time capacity (mAh) 100 times capacity retention rate (%) Example 1 61.9 97 Example 2 62.3 99 Example 3 61.5 93 Example 4 61.3 90 Comparative Example 1 60.9 50 Comparative Example 2 61.0 65 Comparative Example 3 61.2 60
[0109] Referring to Table 3, it was confirmed that in the case of Examples 1 to 4 according to the present disclosure, the density of the lithium plating layer increased and the life characteristics were excellent compared with Comparative Examples 1 to 3 having different metal types or compositions. In particular, it was confirmed that Example 2 having a thick thickness of the current collector exhibited the most excellent life characteristics.
[0110] In addition, when Examples 1 to 4 are examined, it can be seen that, even among the metal substrates, the higher the theoretical capacity of the material alloyed with lithium, such as Si or Sn, the more favorable the lifespan.
[0111] Those skilled in the art will appreciate that, based on the above description, various applications and modifications may be made without departing from the spirit and scope of the present invention.
[0112]
Industrial Applicability
[0113] As described above, the lithium-free battery according to the embodiment of the present disclosure adopts a metal capable of alloying with lithium as a metal substrate, so that a lithium-metal alloy layer is formed on the metal substrate by charging, and a lithium plating layer is formed on the lithium-metal alloy layer, thereby effectively increasing the electrodeposition density of the lithium plating layer, thereby minimizing side reactions with the electrolyte and improving life characteristics.
Claims
1. A lithium-free battery comprising a positive electrode, a negative electrode, a separator and a lithium non-aqueous electrolyte, wherein the negative electrode comprises, a metal substrate comprising at least one metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd and Hg and having a thickness of 3 μm to 100 μm, a lithium-metal alloy layer formed on the metal substrate; and a lithium plating layer formed on the lithium-metal alloy layer, The metal contained in the lithium-metal alloy layer is the metal contained in the metal substrate.
2. The lithium-free battery according to claim 1, wherein: The lithium-metal alloy layer and the lithium plating layer are formed by charging the lithium-free battery.
3. The lithium-free battery according to claim 2, wherein: The capacity per unit area of the positive electrode (mAh / cm 2 ) is greater than the capacity per unit area of the negative electrode.
4. The lithium-free battery according to claim 1, wherein: The metal substrate includes at least one metal selected from the group consisting of Si, Ge, Sn, Sb, Mg, Bi, As, Pb, and Zn.
5. The lithium-free battery according to claim 1, wherein: The metal substrate has a thickness of 10 μm to 80 μm.
6. The lithium-free battery according to claim 1, wherein: The lithium-metal alloy layer and the lithium plating layer each have a thickness of 0.1 μm or more.
7. A method for preparing the lithium-free battery of claim 1, the method comprising the following steps: (a) forming a positive electrode mixture layer on at least one surface of a positive electrode current collector to prepare a positive electrode; (b) preparing a preliminary negative electrode composed of a metal substrate, wherein the metal substrate comprises at least one metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd and Hg; (c) providing a separator between the positive electrode and the preliminary negative electrode to prepare an electrode assembly; and (d) placing the electrode assembly and the lithium nonaqueous electrolyte in a battery case, sealing the battery case, and then charging the battery, The positive electrode has a unit area capacity (mAh / cm 2 ) is greater than the capacity per unit area of the negative electrode.
8. The method for preparing a lithium-free battery according to claim 7, wherein: The metal substrate includes at least one metal selected from the group consisting of Si, Ge, Sn, Sb, Mg, Bi, As, Pb, and Zn.
9. The method for preparing a lithium-free battery according to claim 7, wherein: The metal substrate has a thickness of 3 μm to 100 μm.